Human Resource in Health Requirements for Implementing the NAPHS under IHR-GHSA at the Federal Level in Pakistan - World Bank (Washington, DC : World Bank, 2022)
Pakistan along with all UN member states has been a signatory to the International Health Regulations (IHR) 2005 which calls for countries to work together to prevent, detect, and respond to public health emergencies under the IHR (2005). The signatory countries have also agreed to work towards Universal Health Coverage and to build resilient health systems which can adapt and respond to the challenges posed by outbreaks and other health hazards and emergencies of national and international concern. The purpose and scope of the IHR (2005) are very broad. According to Article 2 of the IHR, the purpose and scope of the Regulations are “to prevent, protect against, control and provide a public health response to the international spread of disease in ways that are commensurate with and restricted to public health risks, and which avoid unnecessary interference with international traffic and trade.” In 2021 with the promulgation of the National Institute for Health (NIH) Ordinance, the reorganization of the NIH to National Public Health Institutes was initiated with the core functions of disease surveillance and response, public health laboratories, and research. This meant that as per the JEE and NAPHS, which lay out the various functions of IHR-GHSA under the three pillars conceptual framework for Integrated Disease Surveillance (IDSR) that comprises Prevent-Detect-Respond capacities, the newly constituted NIH required an assessment of current and future health workforce capacities in the country The findings in the report are organized by the three pillars of IDSR:1) Prevent, 2) Detect, and 3) Respond. The gap analysis identified the number of additional health workforce needed in various categories. This review concluded that most of the departments in both animal and human health sectors had urgent requirements for filling existing sanctioned posts as well as for additional workforce. Engagement of the requisite workforce, also requires training needs to be met among the 13 areas of work.